Pengalaman Masyarakat Adat Dalam Memperjuangkan Hak-haknya - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Social,economic,culturaland ecologicalproblemsemergedin Benua Simpakng, WestKalimantansincemodemtimbercompanyhaveexploitedforestof thearea.TheexistenceofAdatcommunityastraditionaolwneroflocalforestisunder threat.Localknowledgen,ormsandvaluesthoseareusefulforconservingnatural resourcesaredisappearing. Policymadebygovernmentgivesmorerightsto the timbercompanytocutingtreesandclearinglandsoftheAdat-ownedarea.Asaresult, conflictinvolvingtheAdatcommunityand thecompanyinevetablyescalates. Someeffortsthathavebeenmadeby theAdatcommunityalongwithan NGOareasfollows: mappingviI/agesares